Androgen pathway resistance in prostate cancer and therapeutic implications - Maughan, Benjamin L (Expert Opin Pharmacother, 2015)
INTRODUCTION: Metastatic prostate cancer is an incurable disease that is treated with a variety of hormonal therapies targeting various nodes of the androgen receptor (AR) pathway. Invariably patients develop resistance and become castration resistant. Common treatments for castration-resistant disease include novel hormonal therapies, such as abiraterone and enzalutamide, chemotherapy, immunotherapy and radiopharmaceuticals. As this disease generally remains incurable, understanding the molecular underpinnings of resistance pathways is critical in designing therapeutic strategies to delay or overcome such resistance. AREAS COVERED: This review will explore the resistance mechanisms relevant to hormonal agents, such as AR-V7 expression and others, as well as discussing new approaches being developed to treat patients with castration-resistant prostate cancer that take advantage of these new insights. A literature search was performed to identify all published clinical trials related to androgen therapy mechanisms of drug resistance in metastatic castration-resistant prostate cancer. EXPERT OPINION: Androgen therapy resistance mechanisms are varied, and include modification of all nodes in the androgen signaling pathway. The optimal treatment for men with relapsed metastatic castration-resistant prostate cancer is uncertain at this time. The authors recommend using available clinical data to guide treatment decision making until more specific biomarkers are clinically available.